2021
DOI: 10.3390/cancers13061471
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Mutant p53 Promotes Resistance to Anti-PD-1-Mediated Oral Cancer Immunoprevention in Carcinogen-Induced Mouse Models

Abstract: Oral squamous cell carcinoma (OSCC) develops through the multistep malignant progression of squamous epithelium. This process can be prevented by PD-1 blockade in a mouse model for oral carcinogenesis. OSCCs exhibit a high incidence of p53 mutations that confer oncogenic gain-of-function (GOF) activities that promote resistance to standard therapies and poor clinical outcomes. To determine whether epithelial p53 mutations modulate anti-PD-1-mediated oral cancer immunoprevention, we generated mouse models for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…This study not only showed the capacity of the hydrogels to control the release of PD-1 antibody and reduce OPL frequency, but also provided evidence of the role of mutant p53 in the mechanism of immunosuppression in OPLs. Other immunoprevention studies using p53 mutant mice have showed similar results but required 8 doses of parental immunotherapy administration (89,123), compared to a single hydrogel-PD1 dose (88). A recent comprehensive study of patient samples of leukoplakia identified that proliferative leukoplakia predicts a high rate of malignant transformation within 5 years of diagnosis.…”
Section: Reversing Immunosuppression In Oplmentioning
confidence: 90%
See 1 more Smart Citation
“…This study not only showed the capacity of the hydrogels to control the release of PD-1 antibody and reduce OPL frequency, but also provided evidence of the role of mutant p53 in the mechanism of immunosuppression in OPLs. Other immunoprevention studies using p53 mutant mice have showed similar results but required 8 doses of parental immunotherapy administration (89,123), compared to a single hydrogel-PD1 dose (88). A recent comprehensive study of patient samples of leukoplakia identified that proliferative leukoplakia predicts a high rate of malignant transformation within 5 years of diagnosis.…”
Section: Reversing Immunosuppression In Oplmentioning
confidence: 90%
“…This carcinogenesis model exhibits similar histological, molecular and chromosomal alterations as observed in human oral carcinogenesis ( 86 , 87 ). We and others have recently reported that 4NQO induced oral lesions expressing mutant Trp53 -R172H contain a higher infiltration of FoxP3+ T regulatory cells (Tregs) compared to Trp53 wild-type mice ( 88 , 89 ). It is known that Tregs are suppressors of antitumor responses that disrupt the maturation of dendritic cells (DC) and prevent the activation of CD4 + effector and CD8 + cytotoxic cells in the tumor microenvironment ( 90 ).…”
Section: Regulation Of the Immune Microenvironment By Genomic Changes...mentioning
confidence: 99%
“…PD-L1 expression is regulated by multiple pathways. The gain-of-function mutant p53 upregulated IL-17 signaling and induced the transformation of infiltrating T cells into exhausted CD8 + T cells to counteract the effects of PD-1 inhibitors ( Wang J. et al, 2021 ). Besides, PD-L1 expression is upregulated by IFN-γ induced immune response, and both wt- and mut-p53 work in this process.…”
Section: How Does P53 Mutation or Deletion Shape An Immunosuppressive...mentioning
confidence: 99%
“…The numbers of cytotoxic T cells, helper T cells, as well as NK cells significantly reduced. Meanwhile, highly immunosuppressive Tregs ( Sallman et al, 2020 ) and M2 macrophages ( Wang et al, 2021 ) are expanded in cases with TP53 mutations.…”
Section: How Does P53 Mutation or Deletion Shape An Immunosuppressive...mentioning
confidence: 99%
“…[3][4][5] To assess the efficacy of PD1 blockade in oral precancers, numerous studies have revealed that PD1 blockade can impede the advancement of oral carcinogenesis in the 4-NQO induced mouse model, which is consistent with our findings. [21][22][23][24][25][26][27][28] Nevertheless, PD1 blockade alone is insufficient to halt or even reverse oral carcinogenesis progression. Given that no studies have systematically characterized the TME, we utilized various platforms to delineate PD1 blockade-induced changes within the TME for oral carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%